Modeling Online Student Engagement Using Social Cognitive Theory - Ashraf Mohamed Abdelaziz Elsayad, Ghada (2021)
This study applied social cognitive theory to investigates the influence of personal and environmental factors on student engagement (concerning the behavioral, emotional, and cognitive engagement dimensions) and, in turn, perceived learning and student satisfaction (as outcomes) in the online learning environment. The study explored the perceptions of Egypt’s higher education students with regard to their engagement, learning, and satisfaction with their online learning experience.